Proteomics reveals a new DNA repair factor involved in DNA damage signaling. (2nd January 2017) - Räschle, Markus
ABSTRACT: Stalling of the DNA replication machinery activates the ATR checkpoint kinase, which coordinates the cellular responses to replication stress. New studies identify a novel ATR activator, ETAA1, which is indispensable for the maintenance of genome integrity. Dysregulation of ETAA1 may contribute to the development of pancreatic cancer.